RET rearrangement-positive pancreatic cancer has remarkable response to pralsetinib: a case report - Zhang, Tongyi; Wang, Hongwei; Cai, Zhiwei; Zhang, Siqi; Jiang, Chongyi (Frontiers in Oncology, 2023)
Patients with metastatic pancreatic cancer have limited treatment options and a dismal prognosis. While RET fusion is rare (0.6%) in pancreatic cancer, the efficacy of RET-targeted treatment in patients with TRIM33-RET fusion has not been previously reported. Herein, we presented a case of a 68-year-old man with pancreatic cancer harboring TRIM33-RET fusion who responded remarkably to pralsetinib despite being intolerant to chemotherapy. To our knowledge, this is the first report on the clinical value of a single TRIM33-RET fusion in pancreatic cancer, which may benefit from the targeted therapy.